Field Testing and Concrete Quality Analysis for Column, Beam and Floor Slab Structures at Siloam Silampari Hospital, Lubuk Linggau City using the Ultrasonic Pulse Velocity (UPV) Method - M. Hasbi Zuher; Zulmahdi Darwis; Soelarso Soelarso; Baehaki Baehaki; Midia Rahma; Abdurohim Abdurohim; Arief Budiman; Ina Asha Nurjanah (Jurnal Fondasi, 2026)
The construction of tall buildings is inextricably linked to various quality standards, which are used to create safe and comfortable buildings for occupants, users, and surrounding buildings. Concrete quality testing is one of the necessary tests performed on construction projects to ensure that towers or tall buildings comply with existing standards and regulations. Testing concrete structures after casting is crucial to ensure they conform to the intended design. Various types of testing can be performed, including non-destructive testing (NDT), semi-destructive testing (SDT), and destructive testing (DT). In this study, we used the Ultrasonic Pulse Velocity (UPV) testing method. Concrete testing using UPV is one of the tests that is more widely used because of the satisfactory results using ultrasonic waves and requires relatively low costs compared to other testing methods. The results obtained were in the Good Concrete Quality Category from the total sample of test points. The minimum concrete compressive strength requirement is 21 MPa for special structural concrete quality based on SNI-2847-2019.